Seroprevalence of human toxocariasis in Latin America and the Caribbean: a systematic review and meta-analysis - Ulloque-Badaracco, Juan R.; Hernandez-Bustamante, Enrique A.; Alarcón-Braga, Esteban A.; Huayta-Cortez, Miguel; Carballo-Tello, Ximena L.; Seminario-Amez, Rosa A.; Rodríguez-Torres, Alejandra; Casas-Patiño, Donovan; Herrera-Añazco, Percy; Benites-Zapata, Vicente A. (Frontiers in Public Health, 2023)
Introduction: The current study aimed to quantitatively synthesize available evidence regarding the seroprevalence of human toxocariasis in Latin America and the Caribbean. Methods: A systematic research involving six electronic databases was conducted using a research strategy that combined MeSH terms with free terms. Article selection and information extraction were performed using a double and independent approach. The Newcastle-Ottawa tool was used to assess the risk of bias in the included articles. The meta-analysis used the random-effects approach, with subgroup analysis and sensitivity analysis for risk of bias also being performed. Results: We included 101 articles with a total of 31,123 participants. The studies were conducted between 1990 and 2022, with Brazil accounting for the largest number of studies (n = 37). The overall seroprevalence of human toxocariasis was 31.0% (95% CI: 27.0-35.0%, I2 = 99%). The prevalence of the main characteristics observed in seropositive patients were as follows: ocular toxocariasis (30.0%), asymptomatic (26.0%), and presence of dogs at home (68.0%). In addition, the seroprevalence was lower in studies including only adults than in those including children or both. In contrast, no differences in seroprevalences were found between studies conducted in the community and hospital. Conclusion: The overall seroprevalence of human toxocariasis in Latin America and the Caribbean was high. Notably, our findings showed that the seroprevalence was increased among populations who kept a dog at home but was decreased in populations comprising only adults. Our findings can be used to establish epidemiological surveillance strategies for the prevention and early identification of toxocariasis.